2021
DOI: 10.3390/ma14030608
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Whey Protein Fibrils with Carbon Nanotubes or Carbon Nano-Onions

Abstract: Whey protein isolate (WPI) fibrils were prepared using an acid hydrolysis induction process. Carbon nanotubes (CNTs) and carbon nano-onions (CNOs) were made via the catalytic chemical vapor deposition (CVD) of methane. WPI fibril–CNTs and WPI fibril–CNOs were prepared via hydrothermal synthesis at 80 °C. The composites were characterized by SEM, TEM, FTIR, XRD, Raman, and TG analyses. The interplay between WPI fibrils and CNTs and CNOs were studied. The WPI fibrils with CNTs and CNOs formed uniform gels and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…The research results of Kang et al [ 32 ] showed that in the case of composite hydrogel based on whey and carbon nanotubes or carbon nano-onions the secondary structure of whey suffered minor changes due to the interactions with carbon based materials; the diffraction peak around 2θ ≈ 20° is still present in the diffraction patterns of composite materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results of Kang et al [ 32 ] showed that in the case of composite hydrogel based on whey and carbon nanotubes or carbon nano-onions the secondary structure of whey suffered minor changes due to the interactions with carbon based materials; the diffraction peak around 2θ ≈ 20° is still present in the diffraction patterns of composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…The spectroscopic analysis in the field of IR (400–4000 cm −1 ) makes a significant contribution to understanding the composition and structure of compounds in the food industry, especially their proteinaceous components [ 16 , 32 , 33 ]. The peptide bonds in the α-helical and β-sheet structures, the coil, and disorganized/random areas of the proteins can be estimated by analyzing the amide I bands (1600–1700 cm −1 ) that correspond with the secondary structure of proteins [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whey is a by-product of the cheese production process, obtained from bovine milk [ 24 ]. The whey protein isolated from it contains peptides, glycopeptides and other protein glycoconjugates with immunomodulating properties such as α-lactalbumins, β-lactoglobulins and components promoting bone mineralization such as calcium, lactates, and phosphates [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, doxorubicin was released through a photo-thermal effect that was triggered by near-infrared light irradiation of the responsive CNTs [ 154 ]. Whey proteins were recently reported to facilitate CNT dispersion within their hydrogels, with CNTs leading to shortening of the protein fibrils that may have useful implications in the development of innovative therapies for amyloidoses [ 173 ].…”
Section: Recent Advancements On Hydrogels With Carbon Nanomaterials For Medicinementioning
confidence: 99%